2020
DOI: 10.46743/2160-3715/2020.4111
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Literary Text Extensive Reading Program through Learning Logs

Abstract: This article reports the findings of action research on the implementation of extensive reading to literary text (henceforth ER) with learning logs (henceforth LL). The research question was: In what ways do the students engage in comprehending literary texts through ER with learning logs? And what are students’ reactions to these activities? The research was conducted in the English Language Education Study Program English Education Department of a state university in Indonesia in which twenty six students vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Additionally, they solved the problems with understanding the QR in ELT texts collaboratively. These findings are in line with the study conducted by Yanto, Saefullah, and Kwary (2020). They found that through learning logs (reading, vocabulary, and grammar), student teachers or PETS demonstrate self-motivation, consciousness, and self-directed learning.…”
Section: The Results Of the Questionnairesupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, they solved the problems with understanding the QR in ELT texts collaboratively. These findings are in line with the study conducted by Yanto, Saefullah, and Kwary (2020). They found that through learning logs (reading, vocabulary, and grammar), student teachers or PETS demonstrate self-motivation, consciousness, and self-directed learning.…”
Section: The Results Of the Questionnairesupporting
confidence: 90%
“…The first six QQs assess students' answers to lesson preparation components such as content objectives, language objectives, content concepts, supplemental resources (i.e., graphs, models, and visuals), content adaptation (i.e., text assignment), and meaningful activities (i.e., learning logs: grammar and vocabulary logs, photo voice, reflective journal, and class-discussion). In particular, the implementation of learning logs (especially grammar and vocabulary logs) has been investigated by Yanto, Saefullah, and Kwary (2020). They reported that to keep track of how well student-teachers or PETS learned new words and language, they used lexico-grammaticall logs (logs for grammar and vocabulary) (YANTO; SAEFULLAH; KWARY, 2020).…”
Section: The Results Of the Questionnairementioning
confidence: 99%